2017
DOI: 10.1017/s0007123417000151
|View full text |Cite
|
Sign up to set email alerts
|

Health and Voting in Young Adulthood

Abstract: Do changes in health lead to changes in the probability of voting? Using two longitudinal datasets, this article looks at the impact of three measures of health – physical health, mental health and overall well-being – on voting trajectories in young adulthood. The results show that self-rated health is associated with a lower probability of voting in one’s first election, depression is related to a decline in turnout over time and physical limitations are unrelated to voting. Some familial resources from chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 48 publications
4
70
0
Order By: Relevance
“…Likewise, health has been linked to various forms of political activity. It has been shown that health problems are linked with a decreased propensity to vote (Couture and Breux [2017]; Goerres [2007]; Mattila et al [2013]; Ojeda and Pacheco [2017]), lower levels of political trust and party choice . The effects of health on forms of political participation other than voting seem to be more varied (Ojeda [2015]; Söderlund and Rapeli [2015]).…”
Section: Party Identification Political Participation and Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, health has been linked to various forms of political activity. It has been shown that health problems are linked with a decreased propensity to vote (Couture and Breux [2017]; Goerres [2007]; Mattila et al [2013]; Ojeda and Pacheco [2017]), lower levels of political trust and party choice . The effects of health on forms of political participation other than voting seem to be more varied (Ojeda [2015]; Söderlund and Rapeli [2015]).…”
Section: Party Identification Political Participation and Healthmentioning
confidence: 99%
“…Our study contributes to the literature in two ways. First, although there is a growing body of research on the effect of health on political participation (e.g., Couture and Breux [2017]; Mattila et al [2013]; Ojeda and Pacheco [2017]; Rapeli et al [2018]), this is the first study to analyse the effect 3 of health on party identification. This is important since studies of the effect of health on behavioural indicators capture its effect as a consequence of party identification and not on the concept itself (Burden and Klofstad 2005), that is, psychological and not behavioural.…”
Section: Introductionmentioning
confidence: 99%
“…So far, much of this has focused on behaviour. We know, for example, that turnout is lower among voters with poor physical health (Schur et al 2002;Mattila et al 2013;Pacheco & Fletcher 2015) or poor mental health -including depression (Ojeda 2015;Sund et al 2017;Burden et al 2017;Couture & Breux 2017;Ojeda & Pacheco 2019;Ojeda & Slaughter 2019). Yet to date we know very little about the impact of psychological health on political attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…In democratic systems, civic engagement -through formal voting, advocacy, and involvement in civic organizations -is one way in which people ensure that governmental and nongovernmental actors work to change laws and policies or take other actions that promote healthy communities. In addition to providing a potential avenue for system change, civic engagement has been shown to be positively associated with physical health (6)(7)(8)(9)(10), health behaviors (11,12), mental health (8,12,13), and well-being (14,15). The specific impact may vary across specific health conditions (16,17).…”
Section: Introductionmentioning
confidence: 99%